Preparation method of hard carbon negative electrode material of high-capacity sodium-ion battery
By preparing high-capacity hard carbon negative electrode materials, using the mixing of biomass raw materials and additives and multi-step processing, the existing hard carbon materials have been solved, and efficient and economical preparation of sodium ion battery negative electrode materials are achieved.
Patent Information
- Application Number
- CN202411462405.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hard charcoal materials have problems with low capacity and first-week efficiency in sodium ion batteries, which limits their commercial development.
By mixing the crushed biomass raw materials with additives, performing low-temperature carbonization, coarse grinding, pickling purification, wet mixing, spray drying and high-temperature sintering, high-capacity hard carbon negative electrode material is prepared.
Hard carbon negative electrode materials with high production efficiency, high capacity and high first-week charge and discharge efficiency are achieved, and the problems of low capacity and efficiency in the prior art are solved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a high-capacity hard carbon negative electrode material for sodium ion batteries. Background Art
[0002] With the rise of the electric vehicle and energy storage markets, there is an increasing demand for low-cost, high-performance new energy storage technologies. Sodium-ion batteries have attracted significant market attention due to their abundant resources, low cost, high safety, and excellent rate performance.
[0003] Currently, common sodium-ion battery anode materials include hard carbon, alloy, and titanium-based materials. Hard carbon materials, with their advantages of widespread availability, low cost, low operating potential, and excellent cycling performance, are currently the mainstream choice for commercialization. However, hard carbon materials still have some limitations, the most significant of which is their relatively low capacity and initial efficiency, which hinder their commercial development.
[0004] However, currently hard carbon mostly uses biomass as raw material, which has the following performance defects: For example, hard carbon materials directly sintered from biomass raw materials have fewer pore structures and therefore lower sodium storage capacity.
[0005] For example, hard carbon materials have a large specific surface area, and the excessive contact area with the electrolyte results in a high irreversible capacity and a low coulombic efficiency in the first cycle. Summary of the Invention
[0006] The purpose of the present invention is to provide a method for preparing a high-capacity hard carbon negative electrode material for sodium ion batteries, which has the characteristics of high production efficiency, high capacity and high first-cycle charge and discharge efficiency.
[0007] The present invention can be achieved through the following technical solutions: The present invention discloses a method for preparing a high-capacity hard carbon negative electrode material for sodium ion batteries, comprising the following steps: S1. Raw material mixing: mixing the crushed biomass raw material with additives to obtain a mixed raw material; S2. Preparation of a precursor: subjecting the mixed raw material obtained in step S1 to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; S3, preparation of a precursor of the first fineness: coarsely grinding the precursor obtained in step S2 to obtain a precursor of the first fineness; S4, precursor purification: the precursor of the first fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor; S5, preparation of a second-fineness precursor: wet-mixing the purified precursor obtained in step S4, a coating agent, and a cross-linking agent, and performing secondary sand milling under controlled temperature to obtain a second-fineness precursor slurry; S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coating precursor; S7, high temperature sintering: The coated precursor obtained in step S6 is subjected to high temperature carbonization under protection to obtain a high-capacity hard carbon negative electrode material.
[0008] Furthermore, in step S3, the D50 of the first fineness is 6-25 μm; and in step S5, the D50 of the second fineness is 3-8 μm.
[0009] In step S3, the coarse grinding particle size will affect the effect of the present invention: if the particle size after coarse grinding is too large, the contact area between the precursor material and the acid solution in step S4 will be small, and it will not be able to fully contact with the acid solution, affecting the purification effect; if the coarse grinding particle size is too small, it will lead to excessive energy consumption of the process, low output, and low yield in the centrifugation process of step S4, which is not conducive to actual production cost control; in step S5, during the sand grinding process, the sand grinding medium generates shear crushing force and extrusion crushing force on the carbon material, so that the material particles are further crushed into small particles, thereby achieving the purpose of further crushing the material particle size. Compared with the commonly used crushing methods (mechanical grinding and air flow powder, etc.) in the hard carbon preparation process, the sand grinding process is more suitable for lightweight materials such as carbon materials, has the advantages of low energy consumption and high efficiency, and is conducive to reducing production costs.
[0010] Furthermore, in step S5, the solid content of the second fineness slurry is 20-50 wt.%, and the sand milling temperature is 30-80°C. During the sand milling process, the slurry gradually heats up due to the heat generated by grinding, so cooling water is required to maintain an appropriate temperature in the sand mill. On the one hand, if the sand milling temperature is too low, the cross-linking reaction will not occur; on the other hand, if the temperature is too high, exceeding the maintenance temperature, it will affect the service life of the equipment.
[0011] Furthermore, in step S2, the conditions for low-temperature carbonization are: a heating rate of 2-20°C / min, a carbonization temperature of 300-900°C, a carbonization time of 1-5 h; and a protective atmosphere of nitrogen and / or argon.
[0012] In step S2, during the low-temperature carbonization process, the biomass raw material is cracked and carbonized at high temperature, gradually transforming from an organic precursor into a carbon material. At the same time, the additive acts as a pore-forming agent, activating the precursor material to form a large number of microporous structures, thereby forming abundant sodium storage active sites in the hard carbon material, thereby increasing the capacity of the hard carbon material. In step S2, the carbonization temperature and carbonization time will affect the effect of the present invention: low carbonization temperature and insufficient carbonization time will result in insufficient activation of the additive, making it impossible to form a sufficient microporous structure in the precursor material; excessively high carbonization temperature and excessively long carbonization time will result in excessive activation and pore collapse, which is also not conducive to the formation of a microporous structure.
[0013] Furthermore, in step S7, the high-temperature carbonization conditions are: a heating rate of 0.5-10°C / min, a carbonization temperature of 900-1600°C, and a carbonization time of 2-15 h.
[0014] In step S7, the coating layer on the surface of the carbon material is carbonized under high temperature to form a dense carbon coating layer, thereby reducing the specific surface area.
[0015] Furthermore, in step S6, the spray drying air inlet temperature is 150-320°C, and the air outlet temperature is 110-130°C. Furthermore, if the temperature is too low, the material cannot be completely dried, and the material moisture content is too high, which will affect the subsequent high-temperature sintering process; if the temperature is too high, the water evaporation rate is too fast, and the additive cannot be evenly distributed on the surface of the precursor material.
[0016] Furthermore, in step S5, the amount of the coating agent added is 1-5 wt% of the amount of the precursor material added; and the amount of the cross-linking agent added is 0.5-1.5 wt% of the amount of the precursor material added.
[0017] In step S5, the coating agent and the cross-linking agent undergo an in-situ cross-linking reaction under the control of temperature and the action of the sanding medium, and polymerize to form a network structure that is evenly coated on the surface of the precursor material; in addition, the cross-linking agent and the functional groups on the surface of the carbon material will also undergo a cross-linking reaction, so that the coating layer and the material are more tightly combined to achieve a better coating effect.
[0018] Furthermore, in step S5, the coating agent is a water-soluble organic small molecule or polymer material, and the water-soluble organic small molecule or polymer material is one or more of glucose, sucrose, water-soluble resin, citric acid, fatty alcohol, glycerol, acetic acid, maleic anhydride, stearic acid, stearyl alcohol, PVP, carboxymethyl cellulose, PAA, PEG, PES, POE, and phenylethanol; the cross-linking agent is a multifunctional small molecule organic substance, and the functional small molecule organic substance is one or more of ethylene glycol, formaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, formic acid, acetic acid, propionic acid, and acetic anhydride.
[0019] Furthermore, in step S1, the amount of the additive added is 20~100wt% of the amount of biomass added; the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal; the additive is one or more of NaOH, KOH, NaCO3, KCO3, H3PO4, ZnCl2, MgCl2, CaCl2, ZnCO3, MgCO3, CaCO3, zinc acetate, magnesium acetate, calcium acetate, zinc oxalate, magnesium oxalate, calcium oxalate, zinc citrate, magnesium citrate, calcium citrate, zinc gluconate, magnesium gluconate, and calcium gluconate.
[0020] Furthermore, in step S3, the pulverization method is one or more of roller mill, jaw crusher, planetary ball mill, mechanical mill, air flow mill and Raymond mill.
[0021] Furthermore, in step S4, the pickling solvent is one or more of hydrochloric acid, nitric acid, hydrofluoric acid, oxalic acid, benzoic acid, and sulfuric acid, the pickling purification temperature is 50-90° C., and the pickling purification time is 5-24 hours.
[0022] The present invention provides a method for preparing a high-capacity hard carbon negative electrode material for sodium ion batteries, which has the following beneficial effects: First, the production efficiency is high. By adopting the secondary sand grinding process to achieve the target particle size through coarse grinding and fine grinding, this process has low energy consumption and high production efficiency compared with traditional air flow grinding and other processes. Second, high capacity: additives are added to the raw materials, which are activated through a subsequent low-temperature carbonization process to construct a rich microporous structure inside the carbon material. Combined with the coating process, the open pores open to the electrolyte are converted into closed pores, thereby increasing the sodium storage capacity of the negative electrode material; Third, the first-cycle efficiency is high. On the basis of the aforementioned fineness control, a dense carbon layer is coated on the surface of the porous carbon material through a coating process to reduce the surface porosity, thereby reducing the contact area between the surface of the hard carbon material and the electrolyte, reducing irreversible capacity loss, and improving the first-cycle efficiency. DETAILED DESCRIPTION
[0023] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below with reference to embodiments.
[0024] The present invention discloses a method for preparing a high-capacity hard carbon negative electrode material for sodium ion batteries, comprising the following steps: S1. Raw material mixing: mixing the crushed biomass raw material with additives to obtain a mixed raw material; S2. Preparation of a precursor: subjecting the mixed raw material obtained in step S1 to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; S3, preparation of a precursor of the first fineness: coarsely grinding the precursor obtained in step S2 to obtain a precursor of the first fineness; S4, precursor purification: the precursor of the first fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor; S5, preparation of a second-fineness precursor: wet-mixing the purified precursor obtained in step S4, a coating agent, and a cross-linking agent, and performing secondary sand milling under controlled temperature to obtain a second-fineness precursor slurry; S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coating precursor; S7, high temperature sintering: The coated precursor obtained in step S6 is subjected to high temperature carbonization under protection to obtain a high-capacity hard carbon negative electrode material.
[0025] Furthermore, in step S3, the D50 of the first fineness is 6-25 μm; and in step S5, the D50 of the second fineness is 3-8 μm.
[0026] Furthermore, in step S5, the solid content of the second fineness slurry is 20-50 wt.%, and the sand milling temperature is 30-80°C.
[0027] Furthermore, in step S2, the conditions for low-temperature carbonization are: a heating rate of 2-20°C / min, a carbonization temperature of 300-900°C, a carbonization time of 1-5 h; and a protective atmosphere of nitrogen and / or argon.
[0028] Furthermore, in step S7, the high-temperature carbonization conditions are: a heating rate of 0.5-10°C / min, a carbonization temperature of 900-1600°C, and a carbonization time of 2-15 h.
[0029] Furthermore, in step S6, the inlet air temperature of the spray drying is 150-320°C, and the outlet air temperature is 110-130°C.
[0030] Furthermore, in step S5, the amount of the coating agent added is 1-5 wt% of the amount of the precursor material added; and the amount of the cross-linking agent added is 0.5-1.5 wt% of the amount of the precursor material added.
[0031] Furthermore, in step S5, the coating agent is a water-soluble organic small molecule or polymer material, and the water-soluble organic small molecule or polymer material is one or more of glucose, sucrose, water-soluble resin, citric acid, fatty alcohol, glycerol, acetic acid, maleic anhydride, stearic acid, stearyl alcohol, PVP, carboxymethyl cellulose, PAA, PEG, PES, POE, and phenylethanol; the cross-linking agent is a multifunctional small molecule organic substance, and the functional small molecule organic substance is one or more of ethylene glycol, formaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, formic acid, acetic acid, propionic acid, and acetic anhydride.
[0032] Furthermore, in step S1, the amount of the additive added is 20~100wt% of the amount of biomass added; the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal; the additive is one or more of NaOH, KOH, NaCO3, KCO3, H3PO4, ZnCl2, MgCl2, CaCl2, ZnCO3, MgCO3, CaCO3, zinc acetate, magnesium acetate, calcium acetate, zinc oxalate, magnesium oxalate, calcium oxalate, zinc citrate, magnesium citrate, calcium citrate, zinc gluconate, magnesium gluconate, and calcium gluconate.
[0033] Furthermore, in step S3, the pulverization method is one or more of roller mill, jaw crusher, planetary ball mill, mechanical mill, air flow mill and Raymond mill.
[0034] Furthermore, in step S4, the pickling solvent is one or more of hydrochloric acid, nitric acid, hydrofluoric acid, oxalic acid, benzoic acid, and sulfuric acid, the pickling purification temperature is 50-90° C., and the pickling purification time is 5-24 hours.
[0035] Example 1 This embodiment relates to a high-capacity hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Raw material mixing: The crushed biomass raw material is mixed with additives to obtain a mixed raw material. Specifically, the amount of additive added is 100 wt% of the biomass added amount; the biomass raw material is walnut shells, nut shells, apricot shells, straw, or reeds; and the additive is NaOH, KOH, or NaCO3.
[0036] S2. Preparation of precursor: The mixed raw material obtained in step S1 is subjected to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; specifically, the conditions for low-temperature carbonization are: a heating rate of 10 °C / min, a carbonization temperature of 300 °C, and a carbonization time of 5 h; the protective atmosphere is nitrogen, S3. Preparation of a precursor of first fineness: The precursor obtained in step S2 is coarsely ground to obtain a precursor with a D50 of 15 μm. Specifically, the coarse grinding method is a double roller method.
[0037] S4. Precursor purification: The precursor of the first fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor. Specifically, the acid washing solvent is hydrochloric acid or nitric acid, the acid washing and purification temperature is 50°C, and the acid washing and purification time is 24 hours.
[0038] S5. Preparation of a Second-Grade Precursor: The purified precursor obtained in step S4, 5 wt% of a coating agent, and 1 wt% of a crosslinking agent are wet-mixed and sand-milled at 30°C to obtain a precursor slurry with a D50 of 8 μm and a solid content of 35 wt%. Specifically, the coating agent is a water-soluble organic small molecule or polymer material such as glucose, sucrose, or a water-soluble resin; the crosslinking agent is a multifunctional small molecule organic compound such as ethylene glycol, formaldehyde, or acetaldehyde.
[0039] S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coated precursor. Specifically, the inlet air temperature of the spray drying is 320°C and the outlet air temperature is 110-130°C.
[0040] S7, high-temperature sintering: The coated precursor obtained in step S6 is subjected to high-temperature carbonization under protection to obtain a high-capacity hard carbon anode material. Specifically, the high-temperature carbonization conditions are: a heating rate of 10°C / min, a carbonization temperature of 1300°C, and a carbonization time of 2 hours.
[0041] Example 2 This embodiment relates to a high-capacity hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Raw material mixing: The crushed biomass raw material is mixed with additives to obtain a mixed raw material. Specifically, the additive is added in an amount of 60wt% of the biomass added; the biomass raw material is eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, or sub-bituminous coal; and the additive is calcium citrate, zinc gluconate, magnesium gluconate, or calcium gluconate.
[0042] S2. Preparation of precursor: The mixed raw material obtained in step S1 is subjected to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; specifically, the conditions for low-temperature carbonization are: heating rate of 2 °C / min, carbonization temperature of 900 °C, carbonization time of 3 h; protective atmosphere of argon, S3. Preparation of a precursor of first fineness: Coarsely grind the precursor obtained in step S2 to obtain a precursor with a D50 of 6 μm. Specifically, the coarse grinding method is planetary ball milling.
[0043] S4. Precursor purification: The precursor of the first fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor. Specifically, the acid washing solvent is benzoic acid and sulfuric acid, the acid washing and purification temperature is 90°C, and the acid washing and purification time is 15 hours.
[0044] S5. Preparation of a Second-Grade Precursor: The purified precursor obtained in step S4, 1 wt% of a coating agent, and 1.5 wt% of a crosslinking agent are wet-mixed and sand-milled at 55°C to obtain a precursor slurry with a D50 of 3 μm and a solids content of 20-50 wt%. Specifically, the coating agent is a water-soluble organic small molecule or polymer material such as glucose, sucrose, PEG, POE, or phenylethanol; the crosslinking agent is a multifunctional small molecule organic compound such as propionaldehyde, glutaraldehyde, formic acid, acetic acid, propionic acid, or acetic anhydride.
[0045] S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coated precursor. Specifically, the inlet air temperature of the spray drying is 220°C and the outlet air temperature is 130°C.
[0046] S7, high-temperature sintering: The coated precursor obtained in step S6 is subjected to high-temperature carbonization under protection to obtain a high-capacity hard carbon anode material. Specifically, the high-temperature carbonization conditions are: heating rate of 5°C / min, carbonization temperature of 900°C, and carbonization time of 15 hours.
[0047] Example 3 This embodiment relates to a high-capacity hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Raw material mixing: The crushed biomass raw material is mixed with additives to obtain a mixed raw material. Specifically, the additive is added in an amount of 20wt% of the biomass added; the biomass raw material is walnut shells, nut shells, anthracite, lignite, or sub-bituminous coal; and the additive is NaOH, magnesium citrate, calcium citrate, zinc gluconate, magnesium gluconate, and calcium gluconate.
[0048] S2. Preparation of precursor: The mixed raw material obtained in step S1 is subjected to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; specifically, the conditions for low-temperature carbonization are: a heating rate of 20 °C / min, a carbonization temperature of 600 °C, and a carbonization time of 1 h; the protective atmosphere is nitrogen and argon, S3. Preparation of a precursor of first fineness: The precursor obtained in step S2 is coarsely ground to obtain a precursor with a D50 of 6-25 μm. Specifically, the coarse grinding method is jaw crushing or mechanical grinding.
[0049] S4. Precursor purification: The precursor of the first fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor. Specifically, the acid washing solvent is hydrochloric acid, benzoic acid, and sulfuric acid, the acid washing and purification temperature is 50°C, and the acid washing and purification time is 24 hours.
[0050] S5. Preparation of a second-fineness precursor: The purified precursor obtained in step S4, 1-5 wt% of a coating agent, and 0.5-1.5 wt% of a crosslinking agent are wet-mixed and subjected to secondary sand grinding at a controlled temperature of 30-80°C to obtain a precursor slurry with a D50 of 3-8 μm and a solid content of 20-50 wt%. Specifically, the coating agent is a water-soluble organic small molecule or polymer material such as carboxymethyl cellulose, PAA, PEG, PES, POE, or phenylethyl alcohol; and the crosslinking agent is a multifunctional small molecule organic compound such as propionic acid or acetic anhydride.
[0051] S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coated precursor. Specifically, the inlet air temperature of the spray drying is 150°C and the outlet air temperature is 120°C.
[0052] S7, high-temperature sintering: The coated precursor obtained in step S6 is subjected to high-temperature carbonization under protection to obtain a high-capacity hard carbon anode material. Specifically, the high-temperature carbonization conditions are: heating rate of 0.5°C / min, carbonization temperature of 1600°C, and carbonization time of 8 hours.
[0053] Example 4 This embodiment relates to a high-capacity hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Raw material mixing: The crushed biomass raw material is mixed with additives to obtain a mixed raw material. Specifically, the additive is added in an amount of 80% by weight of the biomass added; the biomass raw material is coffee husks, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, or oak; and the additive is ZnCO3, MgCO3, CaCO3, zinc acetate, zinc gluconate, magnesium gluconate, and calcium gluconate.
[0054] S2. Preparation of precursor: The mixed raw material obtained in step S1 is subjected to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; specifically, the conditions for low-temperature carbonization are: a heating rate of 4°C / min, a carbonization temperature of 80°C, and a carbonization time of 2h; the protective atmosphere is nitrogen, S3. Preparation of a precursor of first fineness: Coarsely grind the precursor obtained in step S2 to obtain a precursor with a D50 of 6-25 μm. Specifically, the coarse grinding method is air flow milling or Raymond milling.
[0055] S4. Precursor purification: The precursor of the first fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor. Specifically, the acid washing solvent is hydrochloric acid, oxalic acid, or benzoic acid, the acid washing and purification temperature is 80°C, and the acid washing and purification time is 7 hours.
[0056] S5. Preparation of a Second-Grade Precursor: The purified precursor obtained in step S4, 4 wt% of a coating agent, and 0.8 wt% of a crosslinking agent are wet-mixed and sand-milled at 70°C to obtain a precursor slurry with a D50 of 4 μm and a solid content of 40 wt%. Specifically, the coating agent is a water-soluble organic small molecule or polymer material such as glucose or sucrose; the crosslinking agent is a multifunctional small molecule organic compound such as ethylene glycol, formaldehyde, acetaldehyde, acetic acid, propionic acid, or acetic anhydride.
[0057] S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coated precursor. Specifically, the inlet air temperature of the spray drying is 250°C and the outlet air temperature is 125°C.
[0058] S7, high-temperature sintering: The coated precursor obtained in step S6 is subjected to high-temperature carbonization under protection to obtain a high-capacity hard carbon anode material. Specifically, the high-temperature carbonization conditions are: a heating rate of 2°C / min, a carbonization temperature of 1500°C, and a carbonization time of 3 hours.
[0059] Example 5 This embodiment relates to a high-capacity hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Raw material mixing: The crushed biomass raw material is mixed with additives to obtain a mixed raw material. Specifically, the additive is added in an amount of 60wt% of the biomass added; the biomass raw material is walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, lignite, or subbituminous coal; and the additive is NaOH, KOH, NaCO3, magnesium oxalate, calcium oxalate, zinc citrate, magnesium citrate, calcium citrate, zinc gluconate, magnesium gluconate, and calcium gluconate.
[0060] S2. Preparation of precursor: The mixed raw material obtained in step S1 is subjected to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; specifically, the conditions for low-temperature carbonization are: heating rate of 14 ° C / min, carbonization temperature of 400 ° C, carbonization time of 4 h; protective atmosphere of argon, S3. Preparation of a precursor of the first fineness: The precursor obtained in step S2 is coarsely ground to obtain a precursor with a D50 of 6-25 μm. Specifically, the coarse grinding method is a double roller mill, air flow mill, or Raymond mill.
[0061] S4. Precursor purification: The precursor of the first fineness obtained in step S3 is subjected to acid washing, centrifugation, and water washing to obtain a purified precursor. Specifically, the acid washing solvent is hydrochloric acid or nitric acid, the acid washing and purification temperature is 50-90°C, and the acid washing and purification time is 9 hours.
[0062] S5. Preparation of a second-fineness precursor: The purified precursor obtained in step S4, 1-5 wt% of a coating agent, and 0.5-1.5 wt% of a crosslinking agent are wet-mixed and sand-milled at 60°C to obtain a precursor slurry with a D50 of 5 μm and a solid content of 40 wt%. Specifically, the coating agent is a water-soluble organic small molecule or polymer material such as glucose, sucrose, a water-soluble resin, citric acid, a fatty alcohol, glycerol, acetic acid, maleic anhydride, stearic acid, or stearyl alcohol; the crosslinking agent is a multifunctional small molecule organic compound such as ethylene glycol, formaldehyde, or acetaldehyde.
[0063] S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coated precursor. Specifically, the inlet air temperature of the spray drying is 280°C and the outlet air temperature is 115°C.
[0064] S7, high-temperature sintering: The coated precursor obtained in step S6 is subjected to high-temperature carbonization under protection to obtain a high-capacity hard carbon anode material. Specifically, the high-temperature carbonization conditions are: heating rate of 8°C / min, carbonization temperature of 1100°C, and carbonization time of 13 hours.
[0065] Application Example 1 This embodiment relates to a hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Raw material mixing: Coconut shell raw material crushed to a certain fineness is mixed with zinc acetate to obtain a mixed raw material. The amount of zinc acetate added is 50 wt.% of the amount of coconut shell added.
[0066] S2. Preparation of a precursor: The mixed raw material obtained in step S1 was subjected to low-temperature carbonization under a nitrogen atmosphere to obtain a low-temperature carbonized precursor. The heating rate was 5°C / min, the carbonization temperature was 600°C, and the carbonization time was 2 h.
[0067] S3, coarse grinding: the precursor obtained in step S2 is coarsely ground using a pair of rollers and a mechanical grinder in sequence to obtain a precursor with D50=15 μm.
[0068] S4, purification: The precursor of a certain fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor. The acid solution used is a mixed acid of hydrochloric acid, nitric acid, and hydrofluoric acid, the reaction temperature is 80°C, and the reaction time is 20 hours.
[0069] S5. Fine Grinding: The purified precursor obtained in step S4, glucose, and ethylene glycol are mixed with deionized water and sand-milled at a predetermined temperature to obtain a sand-milled slurry. The amounts of glucose and ethylene glycol added are 2 wt.% and 0.8 wt.% of the precursor material, respectively. The sand-milled slurry has a solids content of 35 wt.% and is sand-milled at a temperature of 60°C until the material has a D50 of 5 μm.
[0070] S6, spray drying and coating: spray drying the sand-milled slurry obtained in step S5 to obtain a coated precursor, wherein the inlet air temperature of the spray drying is 230°C and the outlet air temperature is 110°C.
[0071] S7, high temperature sintering: The coated precursor obtained in step S6 is subjected to high temperature carbonization under nitrogen gas protection, with a heating rate of 2°C / min, a carbonization temperature of 1400°C, and a carbonization time of 3 h to obtain a high-capacity hard carbon negative electrode material.
[0072] The electrochemical performance of the obtained material was tested according to the following method: the hard carbon material, Super P, CMC, and SBR of Application Example 1 were mixed into a slurry in a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on a copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a sheet puncher, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and a PP / PE / PP three-layer diaphragm as the diaphragm, and assembled into a CR2032 type button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests with a current density of 0.1C (1C-300 mAh / g) and a voltage range of 2-0.005V.
[0073] Comparative Example 1 This embodiment relates to a hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Raw material mixing: Coconut shell raw material crushed to a certain fineness is mixed with zinc acetate to obtain a mixed raw material. The amount of zinc acetate added is 50 wt.% of the amount of coconut shell added.
[0074] S2. Preparation of a precursor: The mixed raw material obtained in step S1 was subjected to low-temperature carbonization under a nitrogen atmosphere to obtain a low-temperature carbonized precursor. The heating rate was 5°C / min, the carbonization temperature was 600°C, and the carbonization time was 2 h.
[0075] S3, coarse grinding: the precursor obtained in step S2 is coarsely ground using a pair of rollers and a mechanical grinder in sequence to obtain a precursor with D50=15 μm.
[0076] S4, purification: The precursor of a certain fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor. The acid solution used is a mixed acid of hydrochloric acid, nitric acid, and hydrofluoric acid, the reaction temperature is 80°C, and the reaction time is 20 hours.
[0077] S5. Fine grinding: The purified precursor obtained in step S4 is mixed with deionized water and sand-milled at a certain temperature to obtain a sand-milled slurry. The solid content of the sand-milled slurry is 35 wt.%; the sand-milling temperature is 60°C; and the material is sand-milled until D50 = 5 μm.
[0078] S6, spray drying: spray drying the sand-milled slurry obtained in step S5 to obtain a coated precursor, wherein the inlet air temperature of the spray drying is 230°C and the outlet air temperature is 110°C.
[0079] S7, high temperature sintering: The coated precursor obtained in step S6 is subjected to high temperature carbonization under nitrogen gas protection, with a heating rate of 2°C / min, a carbonization temperature of 1400°C, and a carbonization time of 3 h to obtain the hard carbon negative electrode material of comparative example 1.
[0080] The electrochemical performance of the obtained material was tested according to the following method: the hard carbon material of comparative example 1, Super P, CMC, and SBR were mixed into a slurry in a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on a copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a sheet puncher, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and a PP / PE / PP three-layer diaphragm as the diaphragm, and assembled into a CR2032 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests with a current density of 0.1C (1C-300 mAh / g) and a voltage range of 2-0.005 V.
[0081] Comparative Example 2 This embodiment relates to a hard carbon negative electrode material for sodium ion batteries, and a preparation method thereof comprises the following steps: S1. Preparation of Precursor: Coconut shell raw material was carbonized at low temperature under nitrogen atmosphere to obtain a low-temperature carbonized precursor. The heating rate was 5°C / min, the carbonization temperature was 600°C, and the carbonization time was 2 h.
[0082] S2. Coarse grinding: The precursor obtained in step S2 is coarsely ground using a pair of rollers and a mechanical grinder in sequence to obtain a precursor with D50=15 μm.
[0083] S3, purification: The precursor of a certain fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor. The acid solution used is a mixed acid of hydrochloric acid, nitric acid, and hydrofluoric acid, the reaction temperature is 80°C, and the reaction time is 20 hours.
[0084] S4. Fine Grinding: The purified precursor obtained in step S4, glucose, and ethylene glycol are mixed with deionized water and sand-milled at a predetermined temperature to obtain a sand-milled slurry. The amounts of glucose and ethylene glycol added are 2 wt.% and 0.8 wt.% of the precursor material, respectively. The sand-milled slurry has a solids content of 35 wt.% and is sand-milled at a temperature of 60°C until the material has a D50 of 5 μm.
[0085] S5, spray drying and coating: spray drying the sand-milled slurry obtained in step S5 to obtain a coated precursor, wherein the inlet air temperature of the spray drying is 230°C and the outlet air temperature is 110°C.
[0086] S6. High-temperature sintering: The coated precursor obtained in step S6 is subjected to high-temperature carbonization under nitrogen gas protection at a heating rate of 2°C / min, a carbonization temperature of 1400°C, and a carbonization time of 3 h to obtain a high-capacity hard carbon negative electrode material.
[0087] The electrochemical performance of the obtained material was tested according to the following method: the hard carbon material of comparative example 21, SuperP, CMC, and SBR were mixed into a slurry in a mass ratio of 94: 1.5: 2: 2.5, and the black slurry was coated on a copper foil using a 120 um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6 mm using a sheet puncher, with metallic sodium as the counter electrode, 1 mol / L NaClO4 EC+DEC (1:1 vol%) as the electrolyte, and a PP / PE / PP three-layer diaphragm as the diaphragm, and assembled into a CR2032 button cell in a glove box. The above button cell was subjected to constant current charge and discharge tests with a current density of 0.1C (1C-300 mAh / g) and a voltage range of 2-0.005 V.
[0088] The electrochemical performance test results of Application Example 1, Comparative Example 1, and Comparative Example 2 are shown in Table 1: Table 1 Electrochemical performance test results of the examples The nitrogen adsorption-desorption test showed that the specific surface areas of Example 1, Comparative Example 1 and Comparative Example 2 were 8.6, 432 and 15.6 m 2 / g. The test results of Comparative Example 1 demonstrate that the additive can effectively build a pore structure within the hard carbon material, thereby increasing the material's specific surface area. Comparison of the test results of Example 1 with those of Comparative Examples 1 and 2 shows that coating can effectively reduce the specific surface area of the hard carbon material, converting open pores on the surface into closed pores within the material, thereby preventing contact with the electrolyte.
[0089] The constant current charge and discharge test measured that the first-week charge capacity of the hard carbon electrode in Application Example 1 was 362 mAh / g, and the first-week efficiency was 92.3%; the first-week charge capacity of the hard carbon electrode in Comparative Example 1 was 224 mAh / g, and the first-week efficiency was 65.3%; the first-week charge capacity of the hard carbon electrode in Comparative Example 2 was 293 mAh / g, and the first-week efficiency was 91.0%. The constant current charge and discharge test results show that the first-week charge capacity and first-week efficiency of Application Example 1 are significantly improved. The reason for the capacity improvement in Application Example 1 is that a large number of pore structures are constructed in the hard carbon material. These pore structures serve as sodium storage active sites and can effectively improve the sodium storage capacity of the hard carbon material; the reason for the first-week efficiency improvement in Application Example 1 is that the coating significantly reduces the specific surface area of the hard carbon material, reduces the contact area between the carbon material surface and the electrolyte, and thereby reduces the irreversible decomposition of the electrolyte, thereby improving the first-week efficiency.
[0090] The above embodiments are merely specific embodiments of the present invention, and their descriptions are relatively specific and detailed. However, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make various modifications and improvements without departing from the scope of the present invention, and such obvious alternatives are all within the scope of protection of the present invention.
Claims
1. A method for preparing a high-capacity hard carbon negative electrode material for sodium ion batteries, characterized in that The following steps are involved: S1. Raw material mixing: mixing the crushed biomass raw material with additives to obtain a mixed raw material; S2, preparation of a precursor: subjecting the mixed raw material obtained in step S1 to low-temperature carbonization under a protective atmosphere to obtain a low-temperature carbonized precursor; S3, preparation of a precursor of the first fineness: coarsely grinding the precursor obtained in step S2 to obtain a precursor of the first fineness; S4, precursor purification: the precursor of the first fineness obtained in step S3 is subjected to acid washing and purification, centrifugation, and water washing to obtain a purified precursor; S5, preparation of a precursor of the second fineness: wet-mixing the purified precursor obtained in step S4, the coating agent, and the cross-linking agent, and performing secondary sand milling under controlled temperature to obtain a precursor slurry of the second fineness; S6, spray drying: spray drying the second precursor slurry obtained in step S5 to obtain a coated precursor; S7, high temperature sintering: the coated precursor obtained in step S6 is subjected to high temperature carbonization under protection to obtain a high capacity hard carbon negative electrode material.
2. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S3, the D50 of the first fineness is 6-25 μm; in step S5, the D50 of the second fineness is 3-8 μm.
3. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S5, the solid content of the second fineness slurry is 20-50wt.%, and the sand milling temperature is 30-80°C.
4. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S2, the conditions for low-temperature carbonization are: a heating rate of 2-20°C / min, a carbonization temperature of 300-900°C, a carbonization time of 1-5 h; and a protective atmosphere of nitrogen and / or argon.
5. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S7, the high temperature carbonization conditions are: heating rate of 0.5-10°C / min, carbonization temperature of 900-1600°C, and carbonization time of 2-15 h.
6. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S6, the inlet air temperature of the spray drying is 150-320°C, and the outlet air temperature is 110-130°C.
7. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S5, the amount of coating agent added is 1-5 wt% of the amount of precursor material added; the amount of cross-linking agent added is 0.5-1.5 wt% of the amount of precursor material added.
8. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S5, the coating agent is a water-soluble organic small molecule or polymer material, which is one or more of glucose, sucrose, water-soluble resin, citric acid, fatty alcohol, glycerol, acetic acid, maleic anhydride, stearic acid, stearyl alcohol, PVP, carboxymethyl cellulose, PAA, PEG, PES, POE, and phenylethyl alcohol; the cross-linking agent is a multifunctional small molecule organic substance, which is one or more of ethylene glycol, formaldehyde, acetaldehyde, propionaldehyde, glutaraldehyde, formic acid, acetic acid, propionic acid, and acetic anhydride.
9. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S1, the amount of additive added is 20~100wt% of the amount of biomass added; the biomass raw material is one or more of walnut shells, nut shells, apricot shells, straw, reeds, coffee shells, coconut shells, bamboo, poplar, eucalyptus, pine, fruit wood, miscellaneous wood, fir, oak, anthracite, lignite, and sub-bituminous coal; the additive is one or more of NaOH, KOH, NaCO3, KCO3, H3PO4, ZnCl2, MgCl2, CaCl2, ZnCO3, MgCO3, CaCO3, zinc acetate, magnesium acetate, calcium acetate, zinc oxalate, magnesium oxalate, calcium oxalate, zinc citrate, magnesium citrate, calcium citrate, zinc gluconate, magnesium gluconate, and calcium gluconate.
10. The method for preparing a high-capacity sodium ion battery hard carbon negative electrode material according to claim 1, characterized in that: In step S3, the pulverizing method is one or more of the following: roller crusher, jaw crusher, planetary ball mill, mechanical mill, air flow mill, and Raymond mill; In step S4, the pickling solvent is one or more of hydrochloric acid, nitric acid, hydrofluoric acid, oxalic acid, benzoic acid, and sulfuric acid, the pickling purification temperature is 50-90°C, and the pickling purification time is 5-24h.
Citation Information
Patent Citations
Preparation method of sodium ion battery negative electrode porous hard carbon
CN118529716A
Hard carbon negative electrode material of fast-charging sodium-ion battery and preparation method of hard carbon negative electrode material
CN118771356A